The Fis Nucleoid Protein Negatively Regulates the Phase Variation fimS Switch of the Type 1 Pilus Operon in Enteropathogenic Escherichia coli - Saldaña-Ahuactzi, Zeus; Soria-Bustos, Jorge; Martínez-Santos, Verónica I.; Yañez-Santos, Jorge A.; Martínez-Laguna, Ygnacio; Cedillo-Ramirez, María Lilia; Puente, José L.; Girón, Jorge A. (Frontiers in Microbiology, 2022)
In Escherichia coli the expression of type 1 pili (T1P) is determined by the site-specific inversion of the fimS ON-OFF switch located immediately upstream of major fimbrial subunit gene fimA. Here we investigated the role of virulence (Ler, GrlR, and GrlA) and global regulators (H-NS, IHF, Fis) in the regulation of the fimS switch in the human enteropathogenic E. coli (EPEC) O127:H6 strain E2348/69. This strain does not produce detectable T1P and PCR analysis of the fimS switch confirmed that it is locked in the OFF orientation. Among the regulator mutants analyzed, only the fis mutant produced significantly high levels of T1P on its surface and yielded high titers of agglutination of guinea pig erythrocytes. Expression analysis of the fimA, fimB, and fimE promoters using lacZ transcriptional fusions indicated that only PfimA activity is enhanced in the absence of Fis. Collectively, these data demonstrate that Fis is a negative regulator of T1P expression in EPEC and suggest that it is required for the FimE-dependent inversion of the fimS switch from the ON-to-OFF direction. It is possible that a similar mechanism of T1P regulation exists in other intestinal and extra-intestinal pathogenic classes of E. coli.